Relationship between photocatalytic activity, hydrophilicity and photoelectric properties of TiO₂ thin films - Kolouch, A.; Horáková, M.; Hájková, P.; Heyduková, E.; Exnar, P.; Spatenka, P. (Вопросы атомной науки и техники, 2006)
TiO₂ thin films were prepared by PECVD technique from vapors of Titanium-IV iso-propoxide mixed with oxygen at different temperatures. The films were deposited on substrates with system of special platinum electrodes and on glass substrates. Photoconductivity and capacitance at different humidity, photocatalytic activity and photo-induced hydrophility under UV irradiation and surface morphology were evaluated on the films. The results revealed that the photoconductivity is influenced by humidity and is connected to the photocatalytic activity.